YIELD AND ITS COMPONENTS OF CORN AT SALINE SODIC SOIL WASHED WITH ENRICHED WATER BY A COMBINATIONS OF PHOSPHOGYPSUM AND HUMIC ACIDS - Akram A. H. Al-Hadethi, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
A field study was conducted during the spring season of 2020 in saline sodic soils with clay loam texture, to study 16 combinations of phosphogypsum and humic acids. A randomized complete block design according to the order of treatment added to the factorial experiment was used with three replications. The experiment included the use of humic acids (HA1, HA2, HA3, and HA4) and phosphogypsum (G1, G2, G3, and G4) in four levels (0.5, 1.0, 1.5, 2.0 g L-1) for both of them mixed in washing water to make 16 combinations, in addition to washing with a commercial clean salt (CS) treatment and Euphrates water only (W) to become 18 treatments. All experimental units were washed with enriched water with combinations and with a commercial clean salt and water. The results showed that washing with HA4G4 combination showed the highest significant increase in Calcium and Magnesium concentration, which reached 194.20 and 60.40 mmol L-1 compared to the rest of the combinations. Also there was a significant decrease in the Sodium adsorption ratio, which reached 0.83. Combination HA4G4 gave a highest significant increase in plant height, dry matter weight, grain yield, the weight of 300 grains, and an increase of 84.605%, 67.00%, 190.79%, and 67.92% compared to washing with water alone (W), respectively. The same combination also showed a highest significant increase in the Nitrogen, Phosphorous, and Potassium content of grains, with an increase of 26.23%, 133.83%, and 150.68% compared to washing with water (W), respectively.